The southern segment of the Famatinian magmatic arc, La Pampa province, Argentina - Chernicoff, Carlos Jorge (2010)
The present study led to the identification of a largely hidden southern segment of the Famatinian magmatic arc in the province of La Pampa, south-central Argentina. The arc is represented by scarce outcrops of metaigneous rocks (mostly meta-quartz-diorites and metagabbros) but stands out in the aeromagnetic data as a conspicuous and continuous, NNW-trending magnetic anomaly. The geochemical signature of this magmatic suite points to a pre-collisional continental magmatic arc. Its crystallization age (U-Pb SHRIMP dating on magmatic zircon) ranges from ca. 476 to 466 Ma, being comparable, therefore, to the central and northern segments of the Famatinian arc. All dated zircon of the metagabbro have similar 176Hf/177Hf ratios, negative eHf (from - 5.02 to - 3.62) and average Lu-Hf model ages of ca. 1.7 Ga, indicating a crustal contamination of a mantle-derived mafic magma (of ca. 466 Ma) with much older rocks, probably older than 2 Ga, hence suggesting that part of the underlying basement of the southernmost Pampia terrane is at least this old. U-Pb SHRIMP dating on metamorphic zircon rims/areas yielded ca 454 Ma, that is within the 465-450 Ma age range of Famatinian metamorphism previously recorded in La Pampa. The amphibolite-facies metamorphism that affects the magmatic arc in La Pampa is attributed to the collision of the Cuyania (greater Precordillera) terrane against the western margin of Gondwana.